Capital Inflows : Macroeconomic Implications and Policy Responses - Elekdag, Selim; Cardarelli, Roberto; Kose, Ayhan (Washington, D.C. : International Monetary Fund, 2009)
This paper examines the macroeconomic implications of, and policy responses to surges in private capital inflows across a large group of emerging and advanced economies. In particular, we identify 109 episodes of large net private capital inflows to 52 countries over 1987-2007. Episodes of large capital inflows are often associated with real exchange rate appreciations and deteriorating current account balances. More importantly, such episodes tend to be accompanied by an acceleration of GDP growth, but afterwards growth has often dropped significantly. A comprehensive assessment of various policy responses to the large inflow episodes leads to three major conclusions. First, keeping public expenditure growth steady during episodes can help limit real currency appreciation and foster better growth outcomes in their aftermath. Second, resisting nominal exchange rate appreciation through sterilized intervention is likely to be ineffective when the influx of capital is persistent. Third, tightening capital controls has not in general been associated with better outcomes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet